2011
DOI: 10.1007/s11689-011-9096-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications may play a role in the developmental consequences of early life events

Abstract: Many aspects of postnatal development are influenced by events before birth, including cognitive and language development. An adverse intrauterine environment, for example secondary to poor maternal nutritional status, multiple pregnancy, or late preterm birth, is associated with increased risks of delayed or impaired childhood development and altered physiology in adulthood that may predispose to increased risk of adult disease. Maternal periconceptional undernutrition and twin conception can both result in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 88 publications
0
21
0
Order By: Relevance
“…A shared family history of LLE may reflect either genetic or environmental influences. The suboptimal fetal growth is consistent with possible epigenetic influences on birth weight [2]. An earlier case control study of 5-year-old children with SLI and controls [14] reported an association of parental learning histories but no statistically significant perinatal events, including birth weight, or maternal exposures to disease.…”
Section: Reviewmentioning
confidence: 56%
See 2 more Smart Citations
“…A shared family history of LLE may reflect either genetic or environmental influences. The suboptimal fetal growth is consistent with possible epigenetic influences on birth weight [2]. An earlier case control study of 5-year-old children with SLI and controls [14] reported an association of parental learning histories but no statistically significant perinatal events, including birth weight, or maternal exposures to disease.…”
Section: Reviewmentioning
confidence: 56%
“…Genetic inquiry could help resolve some of the interpretive questions. There is increasing technical documentation of the powerful ways in which genes and gene expression influence development, at the cellular level and also at the cortical level, and how genes and gene expression influence the emergence (and decline) of general cognitive abilities in animal models as well as for human development [2-5,36,37]. Although the biological mechanisms are yielding to experimental methods, there is a large gap in the empirical human evidence base, particularly at the level of detailed longitudinal description of children’s language acquisition over the years encompassing the transition from child language to adult language.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent issue (vol 3, issue 4) [2] included papers on Turner Syndrome, Autism Spectrum Disorder, Prader-Willi Syndrome, William's Syndrome, Fragile X, Specific Language Impairment and Stuttering, and covered a wide-range of cross-cutting perspectives from the effects of prenatal exposures on risk for autism to the impact of sex differences on the developing brain. In this same issue, the Special Section entitled 'Building an Epigenetics Perspective on Language, Speech and Reading Impairments', edited by Mabel Rice [3], examined in more detail genetic mechanisms underlying disorders of communication. Clearly this new Journal has met the challenge of integrating across multiple perspectives and over multiple levels of analysis.…”
Section: Editorialmentioning
confidence: 99%
“…Among the most likely are atypical levels of corticotropin releasing hormone (CRH) and cortisol that are associated with PTSD and which have been shown to impact important aspects of reproduction, including the timing of delivery and weight of infants at birth (Morland et al 2007; Seng et al 2011; Wadhwa 2005). In addition, PTSD could affect women’s antenatal health via immune dysfunction (review in Pace and Heim, 2011), altered gene expression (Bloomfield 2011), and maladaptive health behaviors (Owen et al 2005; Seng et al 2008; Yampolsky et al 2010) - any one of which could ultimately lead to a disproportional loss of weaker embryos/fetuses, which are more likely male (Elsmén et al 2004). Other possibilities include stress-related increases in androgens during pregnancy, which could affect fetal development especially among males (James, 2012).…”
Section: Discussionmentioning
confidence: 99%